Behavior of Cellulose Biosynthetic Membrane as a Peritendinous Implant in Foals - Schade, Jackson; Gomes das Neves Oliveira, Maria Eduarda; Silva de Souza, Renato; Deconto, Ivan; Timboni Teixeira, William; Luizari Guedes, Rogério; Froes, Tilde; Rodrigues Silva-Meirelles, Jéssica; D’Otaviano de Castro V, Ricardo Guilherme; Triches Dornbusch, Peterson (Acta Scientiae Veterinariae, 2019)
Background: Tendon injuries are common in horses and are commonly associated with lameness and athletic career disruption. Adhesions formed between the tendons and the surrounding tissues compromise the sliding and movement of the structures, compromising their functionality. Therefore, the control of adhesion formation is critical to restore the structural integrity of the tendon, as well as its biomechanical function. The aim of this study was to evaluate the behavior of the biosynthetic cellulose membrane implanted in foals with surgically induced tendinitis of the superficial digital flexor. Materials, Methods & Results: Six healthy foals were used, which underwent tendinitis induction in the superficial digital flexor of the right and left forelimbs. The lesions was induced by local ischemia by crushing the tendon with hemostatic forceps. The biosynthetic cellulose membranewas implanted only in the right forelimb, involving the superficial digital flexor tendon in the region of the ischemia and the left forelimb was used as control. After surgery, both forelimb were immobilized with synthetic plaster cast for 15 days. Ultrasonography was performed in six foals immediately before (M0), at 15° (M1) at and 30° (M2) day, and three were evaluate at 45° (M3) and 60° (M4) day after surgery. Incisional biopsies were performed in three animals on the 30° day and in three animals on the 60° day after surgery. Histopathological examination involved the analysis of tissue disorganization, presence and type of inflammatory infiltrate and neovascularization, according to the score of 0 to 3. Ultrasonography allowed visualization of the membrane, which was characterized as a continuous hyperechoic line at the edges of the tendon at 15 days (M1). In addition, at 30 and 45 days after surgery, interruption of the hyperechoic line and reduction of echogenicity were observed, and no echogenic lines were observed at 60 days after surgery. During the biopsies, the fragments obtained from the treated limb were presented with easily detachable layers and separate layers of tissue during histological cutting and the slides preparations. There was no significant difference in relation to the histopathological scores between the treated and control member. The inflammatory infiltrate was predominantly of mononuclear cells and fibroblasts, with identification of giant cell in a foal at 30 days. Neovascularization was observed in all limbs, treated and controls at 30 days and in two treated limbs and three control at 60 days. It was possible to identify the synthetic cellulose membrane by histopathology in only two limbs treated at 30 days and in no limb at 60 days. Discussion: The degree of tendonitis induced in the present study was considered mild according to ultrasonographic analysis at 15 days after surgery. This fact limited the evaluation of the biosynthetic cellulose membrane in the prevention of adhesions, since they were not observed in both groups. However, the ability of the membrane to minimize adhesion formation can be suggest by the macroscopically observed individualization of the tissue layers during histological sections and slides preparation. Ultrasonographic analysis allowed the visualization of the membrane, as well as its positioning and the absorption process. Therefore, ultrasonography can be used in post-implantation monitoring of the membrane. The comparison of the histopathological scores demonstrates the biocompatibility of the biosynthetic cellulose membrane when implanted in foals submitted to surgically induced tendinitis, since there was no difference when compared to treated and control limbs. Therefore, it can be used safely in the treatment of tendon injuries in horses.